A COMPARATIVE ANALYSIS BETWEEN PHOSPHATES AND SILICATES-BASED DENTIFRICE TOOTHPASTES - Laura Ecaterina Romila; Alina Monica Miftode; Ionut Iulian Lungu; Daniela Ivona Tomita; Mihaela Papusa Vasiliu; Diana Gheban; Norin Forna; Constanta Mocanu; Alina Stefanache (Romanian Journal of Oral Rehabilitation, 2024)
Aim of the study: Toothpaste, an indispensable component of oral hygiene routines, has witnessed a remarkable evolution from ancient times to the present era of scientific rigor. This study explores the differences in toothpaste formulations, focusing on the integration of active compounds, abrasive agents, stabilizers, and anticorrosive measures.